'Closing the Life Cycle' of Andricus quercuslanigera (Hymenoptera: Cynipidae). (28th March 2018) - Hood, Glen R; Zhang, Linyi; Topper, Leah; Brandão-Dias, Pedro F P; Del Pino, Gaston A; Comerford, Mattheau S; Egan, Scott P
Abstract: While the alternation of asexually and sexually reproducing generations is common among the oak gall wasps (Hymenoptera: Cynipidae: Cynipini), it has been hypothesized that the diversity of taxa displaying this unique life cycle is underestimated because either 1) the alternative generation has not yet been described or 2) each generation is currently described as two distinct species and should be collapsed into one heterogonic organism (referred to as 'closing the life cycle'). Through field observations, experimental rearing, morphological identification, laboratory behavioral assays, and genetic analysis, we demonstrate heterogony in the cynipid species Andricus quercuslanigera (Ashmead 1881 ) (Hymenoptera: Cynipidae), which was previously only described from the asexual generation. We confirm that the asexual generation, which develops in 'fuzzy' galls on the central vein on the underside of leaves on live oaks in southeast Texas, Quercus virginiana, represents only one generation in a bivoltine life cycle that alternates with a newly discovered sexual generation that develops in galls on catkins on the same host. Our study highlights the need for detailed inspections of the life cycles of unisexual gall wasp species and we discuss the closure of the A. quercuslanigera life cycle in light of recent advances in the study of the ecology and evolution of heterogony in the Cynipidae.